2010
DOI: 10.1007/s00296-010-1556-5
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of thyroid disorders in systemic lupus erythematosus

Abstract: To study the spectrum of thyroid disorders in systemic lupus erythematosus (SLE). Hundred SLE patients as per American Rheumatology Association(ARA) classification criteria underwent clinical examination, including assessment of disease activity (SLEDAI) and laboratory evaluation for serum triiodothyronine (T3),free thyroxine (FT4), thyroid stimulating hormone (TSH), antithyroperoxidase (TPO) antibody and antithyroglobulin (TG) antibody. Hundred age- and sex-matched apparently healthy individuals served as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 29 publications
5
78
4
6
Order By: Relevance
“…Kumar et al 31 found that the presence of thyroid dysfunction was greater in patients with high degrees of disease activity, as measured using SLEDAI, while other studies had contrary findings. 32,33 We did not find any association either with activity or with the cumulative harm index.…”
Section: Discussionmentioning
confidence: 85%
“…Kumar et al 31 found that the presence of thyroid dysfunction was greater in patients with high degrees of disease activity, as measured using SLEDAI, while other studies had contrary findings. 32,33 We did not find any association either with activity or with the cumulative harm index.…”
Section: Discussionmentioning
confidence: 85%
“…These diseases have confirmed an increased prevalence among patients with thyroid disorders [5,6,7,8,9]. Based on the immunological pathogenesis of OLP, previous research has shown the presence of serum antibodies to thyroglobulin and thyroid microsomal antibodies in OLP patients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…8,17 Multifactorial thyroid disorders are frequent in SLE patients, in which higher prevalence of hypothyroidism as well as of thyroid autoantibodies detection is widely described. 41,42 However, we did not have cases of thyroid disorders at the onset of this study, since we did not evaluate periodically the thyroid function of these patients.…”
Section: Figurementioning
confidence: 99%
“…8,17 Multifactorial thyroid disorders are frequent in SLE patients, in which higher prevalence of hypothyroidism as well as of thyroid autoantibodies detection is widely described. 41,42 However, we did not have cases of thyroid disorders at the onset of this study, since we did not evaluate periodically the thyroid function of these patients.This study adds evidence against an interference of steroids on sCysC levels, but further randomized studies are certainly necessary to evaluate this possible association to avoid misinterpretation of this GFR marker, in patients under treatment with glucocorticoids. …”
mentioning
confidence: 99%